2017
DOI: 10.1007/s11764-017-0625-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and moderators of a web-based tailored intervention for cancer survivors on social and emotional functioning, depression, and fatigue: randomized controlled trial

Abstract: PurposeThe web-based computer-tailored Kanker Nazorg Wijzer (Cancer Aftercare Guide) supports cancer survivors with psychosocial issues during cancer recovery. The current study investigates whether the 6-month effects in increasing emotional and social functioning and reducing depression and fatigue hold at 12 months from baseline. Moreover, it explores whether patient characteristics moderate the 6- and 12-month intervention effectiveness.MethodsCancer survivors from 21 Dutch hospitals (November 2013–June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 72 publications
1
86
0
Order By: Relevance
“…Forty additional publications were retrieved reporting their needs assessment (n = 18), their step 4 (n = 3), their implementation planning (n = 1), their evaluation (n = 17), and their implementation (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty additional publications were retrieved reporting their needs assessment (n = 18), their step 4 (n = 3), their implementation planning (n = 1), their evaluation (n = 17), and their implementation (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Forty additional publications were retrieved reporting their needs assessment [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (n = 18), their step 4 [52][53][54] (n = 3), their implementation planning 55 (n = 1), their evaluation [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] (n = 17), and their implementation 73 (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…For some studies, we found multiple manuscripts associated with the same intervention 31,33,43,53,56,68 where separate outcomes [69][70][71] or long-term outcomes were reported. 69,70,[72][73][74][75][76][77] We combined these manuscripts as one study, using the author's name associated with the earliest publication date, and linked corresponding manuscripts by listing them under the related outcomes.…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…[INSERT CBT is adaptable across clinical presentations and recently published trials include tailoring for: FCR [45*,51*]; clinically-elevated distress [40]; insomnia [36,39,40,44,48]; sexual dysfunction [43,55]; depression and/or anxiety [33,40,41**,47,50*]; fatigue [49]; symptom clusters [35,46]; hot flushes [34]; and broader non-specific psychosocial coping [53][54][55] Whilst this evidence is promising, much of it derives from trials under 'ideal' conditions. Few pragmatic trials have been conducted, and it remains unclear how well CBT works in 'real world' settings -for example, in patients with complex physical or psychological comorbidities.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%